Audit Keamanan Sistem Informasi Pada Bagian Desktop Management Berdasarkan Standar ISO 27002:2005 Di PT. Telkom Divre V Jatim - Permata, Dian Ayu; Sutanto, Teguh; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Desktop management section PT Telkom Regional Division V East Java has an important role in meeting the needs of employees working facilities . If the process isn’t going well , it can hamper the company's business processes . The section hasn’t been audited , therefore it is necessary to audit.Audit conducted by Telkom policy document with numbers: KD.57 / HK-290 / ITS-30/2006 which have been adapted to ISO 27002: 2005. Audit carried out through four stages: planning, preparation, execution, and reporting. Clause used are clauses 8, 9, and 11.of the audit results, obtained findings on clause 8 are poor employees of company policy, clause 9 namely there emergency exit used to review out access goods and in clause 11 that the co-worker who entrust each password. Recommendations to the findings of clause 8 is added the consequences of the policy document the company in accordance offense, to clause 9 immediately give special procedures so that the emergency exit is used for emergencies only and to clause 11, immediately repair mechanisms to control access to information by making ladder level password security on the application used.Keywords: Audit, ISO 27002:2005, Information Systems Security, Desktop Management